2020
DOI: 10.1111/1744-7917.12851
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormone 20‐hydroxyecdysone promotes CTL1‐mediated cellular immunity in Helicoverpa armigera

Abstract: Mermithid nematodes, such as Ovomermis sinensis, are used as biological control agents against many insect pests, including cotton bollworm (Helicoverpa armigera). However, given the host's robust immune system, the infection rate of O. sinensis is low, thus restricting its widespread use. To understand the host defense mechanisms against mermithid nematodes, we identified and characterized a protein involved in the recognition of O. sinensis, the potential O. sinensis-binding protein C-type lectin 1 (HaCTL1a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that fungal infections alter the insect ecdysone levels [ 41 ], and ecdysone functions critically in modulating the expression of immune-related genes and immune reactions [ 42 , 43 ]. To investigate whether M. rileyi infection alters the ecdysone levels, the hemolymph collected from larvae at 12 and 48 hpi of blastospores or PBS was used for the measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that fungal infections alter the insect ecdysone levels [ 41 ], and ecdysone functions critically in modulating the expression of immune-related genes and immune reactions [ 42 , 43 ]. To investigate whether M. rileyi infection alters the ecdysone levels, the hemolymph collected from larvae at 12 and 48 hpi of blastospores or PBS was used for the measurement.…”
Section: Resultsmentioning
confidence: 99%
“…The functions of insect CTLs in innate immunity include encapsulation, phagocytosis, opsonization, nodule formation, agglutination, melanisation, and prophenoloxidase to combat viral, nematode, and fungal infection [31][32][33][34]36]. For example, the CTL IML-10 in the Asian corn borer Ostrinia furnacalis Guenée (Lepidoptera: Crambidae) is secreted by the fat body into the larval plasma to encapsulate foreign objects [37].…”
Section: Discussionmentioning
confidence: 99%
“…20E-HaEcR-HaUSP, a complex formed by the steroid hormone 20hydroxyecdysone (20E), ecdysone receptor (HaEcR) and ultraspiracle (HaUSP), stimulates expression of CTL1 in H. armigera. Subsequently, HaCTL1 participates in cellular immunity (encapsulation and phagocytosis) to resist invading pathogens (nematodes and bacteria) (137). In addition, HaCTL3 promotes phagocytosis of hemocytes by bacteria (such as E. mundtii), and AMPs regulated by HaCTL3 exert a bactericidal effect.…”
Section: Ctlmentioning
confidence: 99%